The role of various biomarkers in the evaluation of styrene genotoxicity - Vodicka, P; Koskinen, M; Stetina, R; Soucek, P; Vodickova, L; Matousu, Z; Kuricova, M; Hemminki, K (Cancer detection and prevention, 2003)
We evaluated our data on the occupational exposure to styrene in lamination workers. The battery of parameters included markers of external and internal exposure and biomarkers of biological effects and susceptibility. DNA repair capacities have been determined in both exposed and control groups. Styrene workplace concentration significantly correlated with styrene concentration in blood, exhaled air and urinary mandelic acid. Haemoglobin and O(6)-styrene oxide (SO)-guanine DNA adducts were significantly higher in exposed subjects as compared to controls and correlated with exposure parameters. In styrene-exposed workers 1-SO-adenine DNA adducts were detected (2.6 per 10(9) dNp), while in controls these adducts were below the detection limit. 1-SO-adenine adduct levels were affected by both acute and cumulative exposure (P=0.001, F=86.0 and P=0.017, F=59.0, respectively) and associated with cytochrome P450 2E1 (CYP2E1) polymorphisms (R(2)=0.442). Mutant frequencies (MF) at the hypoxanthine-guanine phosphoribosyltransferase (HPRT) locus appeared to accumulate with exposure over time and were associated with glutathione S-transferase P1 (GSTP1) polymorphism. DNA repair capacity increased with the exposure, except for the group exposed to the highest styrene concentration. In this particular group, increased DNA repair capacity to remove oxidative DNA damage was found.
Keywords: Hypoxanthine Phosphoribosyltransferase; Occupational Exposure; Oxidative Stress; hypoxanthinfosforibosyltransferasa; oxidační stres; Humans; lidé středního věku; polymorfismus genetický; oprava DNA; mutační analýza DNA; Female; dospělí; Genotype; lidé; Biomarkers; Cytochrome P-450 CYP2E1; Styrene; Polymorphism, Genetic; Glutathione Transferase; DNA Repair; Adult; DNA Mutational Analysis; styren; biologické markery; ženské pohlaví; Male; cytochrom P-450 CYP2E1; Middle Aged; pracovní expozice; poškození DNA; DNA Damage; genotyp; mužské pohlaví; glutathiontransferasa; adukty DNA; DNA Adducts